Comportamento leitor e processamento de informação em postagens de grupos de whatsapp - Santos, Emerson Gonzaga dos (2022)
This study aimed at investigating how different types of texts posted in WhatsApp groups affect reader behavior, levels of comprehension and the degree of retention of textual information. The research was based on a psycholinguistic perspective, including studies on reading behavior in digital environment (SHIMRAY; KEERTI; RAMAIAH, 2015; LIU; HUANG, 2016), on reading comprehension (DAY; PARK, 2005; KINTSCH; RAWSON, 2013; PERFETTI; LANDI; OAKHILL, 2013; PROTOPSALTIS; BOUKI, 2005VAN DIJK; KINTSCH, 1983) and on recall of text information (BADDELEY, 2010; MENEGASSI, 2010; WOELFER; TOMICH, 2019; YEARI, 2017). Thirty male and female students in higher education, between 18 and 30 years old, participated in WhatsApp groups, the setting in which data were collected in three different tasks in distinct moments. The first task was an online questionnaire whose purpose was to learn about participants’ general reading habits as well as about reading online and on social media, besides others issues such as access to the Internet, use of smartphones etc. The second task consisted of reading and discussing texts posted in the WhatsApp groups so that the six levels of comprehension (DAY; PARK, 2005) were analyzed based on the comments posted about each text. The third task was a test which measured the degree of retention of the information previously read and discussed in the groups. Regarding participants’reading behavior, it was observed that most of them accessed WhatsApp every day and spent around five or more hours reading posts/texts on this social media. While reading on the screen, participants spent most of the time browsing, locating keywords, avoiding rereading texts and doing selective reading, reading only parts of the text and/or looking for the main idea. Participants demonstrated a dispersive behavior, performing more than one task at a time, often not being able to focus on what they were reading due to distractions caused by smartphone notifications, for example. Half of the participants reported that they quickly forgot what they had just read online and, consequently, in WhatsApp groups. It was also observed that levels of reading comprehension varied according to the type of text. Shorter texts generated a bigger number of posts. Data allowed us to state that the participants presented good levels of reading comprehension, above fifty percent, except at the level of reorganization of information. Pearson Chi-square tests indicated a significant relation between participants’ comments - pertinent - and the types of text (p<0,0001), that is, the levels of reading comprehension observed in the comments on the texts posted in the WhatsApp groups varied according to the types of texts. In relation to the degree of retention of the information in the texts posted and discussed in the WhatsApp groups, the results of the tests demonstrated that participants retrieved more literal than inferential information from all types of texts. This suggests that recalling inferences is a more complex and difficult task. Statistic tests yield a significant relation between the type of text and the type of question in the recall tests (p<0,0001); the number of right answers to the questions that tested the recall of literal information in the Text of Official Communication was larger than the ones that tested the retention of literal information in the Fake News Text and in the Long News Text. It is expected that this research contributes to the to the field of studies on text processing in general, and more specifically to the comprehension and retention of information posted in WhatsApp groups, one of the most popular digital social media in Brazil.